HUBUNGAN ANTARA INDEKS MASSA TUBUH (IMT) KATEGORI UNDERWEIGHT DENGAN TINGKAT NYERI DYSMENORRHEA PRIMER PADA REMAJA PUTRI SEKOLAH MENENGAH PERTAMA - Kadek Kristina Harum Lasmi; Ari Wibawa; I Made Muliarta (Majalah Ilmiah Fisioterapi Indonesia, 2017)
ABSTRACTThe Research aims to determine the association between body mass index underweight with primary dysmenorrheapain level. Analytical research design cross sectional approach. Sample technique is systematic random sampling.The sample size is 52 female teenagers in SMP N 9 Denpasar and SMPK Santo Yoseph Denpasar. The technique ofchi square test data analysis. The result of this research is the most mild pain level in normal body mass index whichis 16 respondent (30,8%), moderate pain level in normal body mass index are 15 respondents (28,8%) and level ofpain The most weight in the body mass index underweight category as many as 4 respondents (7.7%). From chisquare test data analysis, p value is 0,041 so p <0,05. Result of statistic test hence can be concluded that there issignificant relation between body mass index underweight with primary dysmenorrhea pain level.Keywords: primary dysmenorrhea, underweight